Hypertrophic Cardiomyopathy Through the Lens of Mitochondria - Tatiana V. Kirichenko; Ivan V. Zhivodernikov; Maria A. Kozlova; Alexander M. Markin; Vasily V. Sinyov; Yuliya V. Markina (Biomedicines)
The mechanisms of pathogenesis of hypertrophic cardiomyopathy are associated with mutations in the sarcomere genes of cardiomyocytes and metabolic disorders of the cell, including mitochondrial dysfunction. Mitochondria are characterized by the presence of their own DNA and enzyme complexes involved in oxidative reactions, which cause damage to mitochondrial protein structures and membranes by reactive oxygen species. Mitochondrial dysfunctions can also be associated with mutations in the genes encoding mitochondrial proteins and lead to a violation of protective functions such as mitophagy, mitochondrial fusion, and fission. Mutations in myofibril proteins can negatively affect mitochondria through increased oxidative stress due to an increased need for ATP. Mitochondrial dysfunction is associated with impaired ATP synthesis and cardiac contractility, leading to clinical manifestations of hypertrophic cardiomyopathy. The current review was designed to characterize the role of mitochondria in the pathogenesis of hypertrophic cardiomyopathy based on published data; the search for publications was based on the analysis of articles including the keywords “hypertrophic cardiomyopathy, mitochondria, dysfunction” in the PubMed and Scopus databases up to January 2025.